Identifikasi Mikroplastik pada 5 Spesies Ikan Laut di TPI Tanjung Beringin Kabupaten Serdang Bedagai - Beatrice Loise Tarigan; Aida Fitriani Sitompul; Mufti Sudibyo (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Microplastic pollution in the marine environment is a global issue that has the potential to threaten aquatic organisms, including marine fish consumed by humans. The presence of microplastics in fish can impact the health of marine ecosystems and risk entering the human food chain. This study aims to analyze the shape, color, abundance, and differences in the abundance of microplastics in the gills and digestive tract of marine fish for consumption. The study was conducted in June-August 2025 at the Tanjung Beringin Fish Farming Site (TPI) in Serdang Bedagai Regency. The sample consisted of five fish species, namely Sardina pilchardus, Selaroides leptolepis, Rastrelliger brachysoma, Parastromateus niger, and Euthynnus affinis, each with 10 individuals/fish species. Microplastics were isolated from the gills and digestive tract, then identified based on the shape and color of the microplastics using a stereo microscope. Microplastic abundance data were analyzed using a one-way ANOVA test. The results showed that the microplastics found were dominated by fibers (56%), fragments (42%), and films (2%). The colors of the identified microplastics included red (81%), black (73%), green (37%), blue (6%), and transparent (3%). The highest microplastic abundance was found in the digestive tract of Euthynnus affinis (41.9 particles/individual), while the lowest was found in the gills of Rastrelliger brachysoma (26.5 particles/individual). The ANOVA test showed significant differences in microplastic abundance (p < 0.05), especially between Sardina pilchardus and Parastromateus niger, and between Selaroides leptolepis and Euthynnus affinis.